Spatial Risk Effects From Lions Compound Impacts of Prey Depletion on African Wild Dogs - Ben Goodheart; Scott Creel; Paul Schuette; Egil Droge; Justine A. Becker; Kambwiri Banda; Anna Kusler; Stephi Matsushima; Kachama Banda; Ruth Kabwe; Will Donald; Johnathan Reyes de Merkle; et al. (Ecology and Evolution)
ABSTRACT Prey depletion threatens many carnivore species across the world and can especially threaten low‐density subordinate competitors, particularly if subordinates are limited to low densities by their dominant competitors. Understanding the mechanisms that drive responses of carnivore density to prey depletion is not only crucial for conservation but also elucidates the balance between top‐down and bottom‐up limitations within the large carnivore guild. To avoid predation, competitively subordinate African wild dogs typically avoid their dominant competitors (lions) and the prey rich areas they are associated with, but no prior research has tested whether this pattern persists in ecosystems with anthropogenically‐reduced prey density, and reduced lion density as a result. We used spatial data from wild dogs and lions in the prey‐depleted Greater Kafue Ecosystem to test if wild dogs continue to avoid lions (despite their low density), and consequently avoid habitats with higher densities of their dominant prey species. We found that although lion density is 3X lower than comparable ecosystems, wild dogs continue to strongly avoid lions, and consequently avoid habitats associated with their two most important prey species. Although the density of lions in the GKE is low due to prey depletion, their competitive effects on wild dogs remain strong. These effects are likely compounded by prey‐base homogenization, as lions in the GKE now rely heavily on the same prey preferred by wild dogs. These results suggest that a reduction in lion density does not necessarily reduce competition, and helps explain why wild dogs decline in parallel with their dominant competitors in ecosystems suffering from anthropogenic prey depletion. Protecting prey populations within the few remaining strongholds for wild dogs is vitally important to avoid substantial population declines. Globally, understanding the impacts of prey depletion on carnivore guild dynamics should be an increasingly important area of focus for conservation.